THERAPEUTIC EFFECTS OF FEEDING GILOY (TINOSPORA CORDIFOLIA) AND FENUGREEK (TRIGONELLA FOENUM-GRAECUM) ON BLOOD BIOCHEMICAL PROFILE IN JERSEY CROSSBRED COWS - Anurag Sharma; Naresh Kumar; Ravindra Kumar; Anika Sharma (Exploratory Animal and Medical Research, 2018)
The study was conducted to evaluate the effect of Giloy (Tinospora cordifolia) and Fenugreek (Trigonella foenum-graecum) supplementation on blood biochemical parameters. The lactating cows were randomly divided into four groups, each group having six animals. T1 , T2 and T3 group cows received Giloy stem powder (150 g), Fenugreek seed powder (150 g), and a combination of both the herbs (75 g of each) respectively, mixed with the concentrate feed for 60 days while the control group (T0 ) received only the concentrate. Blood sampling was done fortnightly, from Day 0 to Day 75. Blood plasma samples were analyzed for biochemical parameters viz. glucose, protein profile (Total protein, albumin, globulin and A: G ratio) and renal profile (urea nitrogen and creatinine). ). It was found that the feeding of Giloy stem powder lead to significantly lower levels (p ≤ 0.05) of blood glucose in the blood of lactating dairy cows. Most of the other blood biochemical parameters remained unchanged in control and treated animals.